Group work : a humanistic and skills building approach - Glassman, Urania (Sage sourcebooks for the human services series (Unnumbered), 2009)
"The Second Edition of Group Work: A Humanistic and Skills Building Approach identifies the humanistic values and democratic norms that guide the group practitioner's interventions. The book presents seven stage themes of group development, 29 techniques for group work practice, and more than 60 new illustrations from contemporary group work. The Second Edition remains centered on the role of the social group work practitioner, who employs group work methods to further the personal growth and empowerment of members in community and institutional contexts."--Jacket